1982
DOI: 10.1002/em.2860040208
|View full text |Cite
|
Sign up to set email alerts
|

Anaphase aberrations: A measure of genotoxicity in mutagen‐treated fish cells

Abstract: Rainbow trout gonad cells (RTG-2) were cultured for various lengths of time in the presence of several classes of known mutagenic chemicals and several related compounds that possessed no known mutagenic/carcinogenic activity. During the course of exposure the cells were examined for the presence of abnormalities in the chromosome arrangement of anaphase figures during mitosis. Untreated and solvent-treated (dimethylsulfoxide-treated) cells exhibited a background abnormality rate of 12% with only minor chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…Therefore, EMN and ENA must be a consequence of nonconjugated metabolites covalently bound to erythrocytic DNA. Furthermore, B(a)P induced DNA adduct formation (Venier and Canova, 1996;Canova et al, 1998) and DNA damage (Bihari et al, 1990;Canova et al, 1998) in mussels, and anaphase aberrations (Kocan et al, 1982), chromosome aberrations (Hooftman, 1981), and hepatocarcinogenicity (Hendricks et al, 1985) in "sh.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, EMN and ENA must be a consequence of nonconjugated metabolites covalently bound to erythrocytic DNA. Furthermore, B(a)P induced DNA adduct formation (Venier and Canova, 1996;Canova et al, 1998) and DNA damage (Bihari et al, 1990;Canova et al, 1998) in mussels, and anaphase aberrations (Kocan et al, 1982), chromosome aberrations (Hooftman, 1981), and hepatocarcinogenicity (Hendricks et al, 1985) in "sh.…”
Section: Discussionmentioning
confidence: 99%
“…From these studies we have shown that fish cells in vitro exhibit chromosomal damage (Kocan et al, 1982), as well as developing mutations (Kocan et al, 1981) much as mammalian cells do. The chromosome damage seen in vitro has also been verified in vivo in our laboratory by Liguori (Ph.d. Thesis, 1984) as well as being described under natural conditions (Longwell & Hughes, 1980).…”
Section: Introductionmentioning
confidence: 97%
“…More subtle abnormalities are identified by irregular cleavages, blister-like outcrops from the body axis and failure of blastopore closure. Detection of cytogenetic defects follows a method determined by Kocan et al (1982), in which numbers of mitotic cells with aberrations at anaphase/telophase are scored to give a relative index. Common malformations include the occurrence of stray chromosomes, attached and free fragments and multi-polar spindles Klumpp and Westernhagen, 1995).…”
Section: Pollutionmentioning
confidence: 99%